Examining factors influencing the emergence of a knowledge society: an explorative study - Zineb ZNAGUI (Je-LKS: Journal of E-Learning and Knowledge Society, 2024)
This article addresses the contextual ambiguity prevalent in the literature surrounding the conceptualizations of a knowledge society. By identifying and clarifying these conceptual challenges, the research aims to provide a solid foundation for understanding the factors influencing the emergence of a knowledge society. The objectives include presenting a clear and comprehensive representation of the multifaceted elements that contribute to this societal transition. Methodologically, a quantitative approach is employed using a regression analysis. The originality of this research lies in its endeavor to develop new perspectives and insights into the catalysts behind the emergence of a knowledge society. By addressing the existing gaps in the literature and employing advanced quantitative methods, the study contributes to the ongoing discourse on the transition to knowledge societies. Practical implications of the research are also developed. The findings offer guidance for policymakers, educators, and stakeholders involved in shaping societal structures, emphasizing actionable insights derived from the identified catalysts. In terms of contribution, this paper provides a nuanced understanding of the factors influencing the knowledge society emergence. By synthesizing empirical evidence with theoretical frameworks, it not only advances academic discourse but also practitioners with valuable insights for informed decision-making in an era characterized by rapid societal transformation.